Paradigms for Bioenergetic Analysis At the dawn of the 21st Century - Tonella, Guy (Bioenergetic Analysis, 2022)
First, basic Lowenian paradigms are first reviewed, followed by updated bioenergetic paradigms, integrating contemporary theoretical and clinical contributions, articulated around the concept of Self: – adaptive motility – sexual motility – motility of attachment Three methodologies are distinguished: – working on conflicts – working on deficits – working on traumas Therapeutic intersubjective relationship is distinguished from analytical relationship. A developmental model from these up-dated bioenergetic paradigms is proposed. Lastly, a sociological approach is outlined as development of bioenergetic technique in a perspective of a «shared world”.